Needs Analysis of Android-Based Science E-Book Development in PGMI Study Programme UIN Mataram - Arizona, Kurniawan; Sucilestari, Ramdhani; Nirmala, Baiq Mutiara Alika (KONSTAN - JURNAL FISIKA DAN PENDIDIKAN FISIKA, 2024)
This study aims to analyse the need for developing Android-based science e-books for PGMI FTK UIN Mataram students. By applying a quantitative approach through questionnaires, this research seeks to identify the needs and characteristics of students in learning science. The results of the analysis showed that 80% of the 45 respondents considered science materials, especially physics content, difficult to understand. The majority of respondents (80%) wanted teaching materials in digital format due to its practicality, effectiveness and efficiency. The very strong support (97.8%) for the development of interactive e-books reflects the urgency of this innovation in improving the quality of learning. The expected e-book is an interactive learning platform with rich multimedia features, while remaining simple and easy to use. E-book development needs to consider student characteristics, such as cognitive and affective development stages, interest in visual materials, and the need for concrete media. In addition, e-book content must be aligned with the competency standards and basic competencies in the applicable curriculum. This research provides a strong foundation for the development of innovative and effective Android-based science e-books to support learning in PGMI Prodi FTK UIN Mataram.